Marcas Linguísticas da imigração na L1 - MENEZES, Mariana Matos (2024)
This paper intends to study the linguistic marks of L2 in L1 (First Language) in the bilingual context of immigration, taking into account the importance of studies in sociology of language and interlanguage for the preservation of Brazilian identity by individuals living abroad and cataloging Brazilian Portuguese spoken by immigrants in Belgium. To carry out this study, vast bibliographical research was developed in heritage language, interlanguage, bilingualism, lexicon, memory and meaning. To execute this research, a qualitative methodology was used through conversations with Brazilian immigrants living in Belgium for more than 10 years. The analysis of the information collected was carried out in light of the previously exposed theoretical framework. Given the results found, it was possible to perceive the influences of the L2 on the L1 of these speakers. It was also possible to identify the change in meaning that some lexical units underwent. Thus, such results constitute relevant elements for future studies, initiatives and strategies aimed at maintaining and using the heritage language in the world.